2014
DOI: 10.1002/nvsm.1516
|View full text |Cite
|
Sign up to set email alerts
|

Are religious people more caring? Exploring the impact of religiosity on charitable organizations in a developing country

Abstract: The purpose of this study is to explore the impact of religiosity on reasons that individuals volunteer. Additionally, this study will investigate the pro-social attitudes towards helping others and charitable organizations. This study focuses on Indonesia where religion plays an important role in daily life. The data were derived from a convenience sampling at a large private university in Surabaya, Indonesia (N = 258). The results showed that individuals with high intrinsic and extrinsic personal religiosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 63 publications
0
14
0
2
Order By: Relevance
“…Implicit ATT is constructed purely based on emotions, as it depends on the feelings of the person at the time of decision making, whereas explicit ATT is declarative; that is, it is based on consciousness, facts, and knowledge. Scholars have argued that both implicit and explicit ATT operate in conjunction during the decision-making process (Argyriou, and Melewar, 2011; Greenwald, and Banaji, 1995).…”
Section: Gaps and Avenues For Future Researchmentioning
confidence: 99%
“…Implicit ATT is constructed purely based on emotions, as it depends on the feelings of the person at the time of decision making, whereas explicit ATT is declarative; that is, it is based on consciousness, facts, and knowledge. Scholars have argued that both implicit and explicit ATT operate in conjunction during the decision-making process (Argyriou, and Melewar, 2011; Greenwald, and Banaji, 1995).…”
Section: Gaps and Avenues For Future Researchmentioning
confidence: 99%
“…Rui, Abreu, Raul, and Dionísio () showed that religiosity influences donation practices. Again, Arli and Lasmono () pointed out that religiosity did not influence attitudes of individuals toward helping others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Religious faith diketahui juga berperan dalam keputusan memilih berkarir pada Faith Based Organization. Religiusitas ditemukan juga berdampak terhadap alasan seseorang menjadi volunteer (Arli & Lasmono, 2015).. Individu yang keputusan karirnya dipengaruhi oleh faktor keagamaan dan spiritualitas mengarahkan karir mereka sebagai bentuk panggilan atau calling (Duffy & Dik, 2009). (Roznowski & Zarzycka, 2020) mengklaim bahwa centrality of religiousity berkaitan positif dengan callingoriented style.…”
Section: Pendahuluanunclassified